Alpha-asarone attenuates depression-like behavior in nicotine-withdrawn mice: Evidence for the modulation of hippocampal pCREB levels during nicotine-withdrawal - Chellian, Ranjithkumar; Pandy, Vijayapandi; Mohamed, Zahurin (Elsevier, 2018)
In the present study, the effect α-asarone on nicotine withdrawal-induced depression-like behavior in mice was investigated. In this study, mice were exposed to drinking water or nicotine solution (10–200 µg/ml) as a source of drinking for forty days. During this period, daily fluid consumption, food intake and body weight were recorded. The serum cotinine level was estimated before nicotine withdrawal. Naïve mice or nicotine-withdrawn mice were treated with α-asarone (5, 10 and 20 mg/kg, i.p.) or bupropion (10 mg/kg, i.p.) for eight consecutive days and the forced swim test (FST) or locomotor activity test was conducted. In addition, the effect of α-asarone or bupropion on the hippocampal pCREB, CREB and BDNF levels during nicotine-withdrawal were measured. Results indicated that α-asarone (5, 10 and 20 mg/kg, i.p.) or bupropion (10 mg/kg, i.p.) pretreatment did not significantly alter the immobility time in the FST or spontaneous locomotor activity in naïve mice. However, the immobility time of nicotine-withdrawn mice was significantly attenuated with α-asarone (5, 10 and 20 mg/kg, i.p.) or bupropion (10 mg/kg, i.p.) pretreatment in the FST. Besides, α-asarone (5, 10 and 20 mg/kg, i.p.) or bupropion (10 mg/kg, i.p.) pretreatment significantly attenuated the hippocampal pCREB levels in nicotine-withdrawn mice. Overall, the present results indicate that α-asarone treatment attenuated the depression-like behavior through the modulation of hippocampal pCREB levels during nicotine-withdrawal in mice.